Norway : Financial Sector Assessment Program-Technical Note-Linkages and Interconnectedness in the Norwegian Financial System. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2015)
This Technical Note reviews linkages and interconnectedness in the Norwegian financial system for Norway. Norway's banks have important connections with global financial centers, but regional links are also important. Norwegian banks are very dependent on global financial centers as sources of funding and to hedge currency risks. Cross-sectoral exposures of Norway's banks, insurance companies, and real estate companies are significant and extend beyond the Nordic region. The authorities are encouraged to expand their current monitoring efforts of crossborder and cross-sectoral exposures of the Norwegian financial sector, and to conduct regional stress tests. For this effect, the authorities can resort to market data and, if available, to balance sheet data of exposures at the individual financial institution level.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet